Peran Pendidikan Karakter Dalam Menghadapi Era Digital - Muchtar, Farah Firdausa; Rahman, Mita Chairunnisa; Azhar, Muthia Nur; Kamila Ishaq, Sehnaz Safana; Wahyudin, Dede; Caturiasari, Jennyta (JURNAL SINEKTIK, 2024)
Character education in this digital era is quite a spotlight in the world of education. The purpose of this research is to examine and understand the "Role of Character Education in Facing the Digital Era" which is related to the social sphere. The research was conducted using the literature study method from a qualitative approach, by searching for and also reading existing written sources such as a book or literature in which there is an explanation related to theoretical studies. The results of this study are seen from several articles that explain character education which has a role when facing the digital era.